Time-based and privacy protection revocable and traceable data sharing scheme in cloud computing - Jiawei ZHANG; Jianfeng MA; Zhuo MA; Teng LI (Tongxin xuebao)
General ciphertext-policy attribute-based encryption (CP-ABE) provides fine-grained access control for data sharing in cloud computing, but its plaintext formed access policy may cause leakage of private and sensitive data.And revoking a malicious user by accurately tracing the identity according to a leaked decryption key is a huge challenge.Moreover, most of existing revocable schemes incur long user revocation list and low efficiency.To solve these problems, a time-based and privacy preserving revocable and traceable data sharing scheme was proposed based on CP-ABE to support expressive monotonic and partial hidden access policy, large attribute universe by conceal the attribute values in access policy.Time-limited data access control using hierarchical identity-based encryption was achieved to set key valid period for users.Moreover, with the approaches of white-box tracing and binary tree, efficient user tracing and direct revocation with shorter revocation list was realized together with high efficiency via online/offline and verifiable outsourced decryption techniques.Furthermore, the scheme was secure under decisional q-BDHE assumption.Theoretical analysis and extensive experiments demonstrate its advantageous performance in computational and storage cost.